Familial localized scleroderma with paediatric onset: a review - Yurtsever, Ida; Łukomska, Małgorzata; Sobolewski, Piotr; Szymańska, Elżbieta; Owczarek, Witold; Walecka, Irena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Localized scleroderma is an inflammatory disease causing sclerosis of the skin. The aetiology and pathogenesis of localized scleroderma remain unclear. Localized scleroderma is considered a genetically driven disease. It is not well understood if genetic factors or environmental exposure individually can cause its development or if their interaction is needed to trigger the disease. Some authors postulate that familial clustering is evidence of a hereditary disease. Familial localized scleroderma has been rarely reported and is a case worth studying. We present the review of literature on this subject with 3 additional cases of familial localized scleroderma with paediatric onset.